2019
DOI: 10.13057/biodiv/d200624
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic identification, nutrients content, bioactive compounds of two jengkol (Archidendron jiringa) varieties from Bengkulu, Indonesia and their potentials as ruminant feed

Abstract: Abstract. Hidayah N, Lubis R, Wiryawan KG, Suharti S. 2019. Phenotypic identification, nutrients content, bioactive compounds of two jengkol (Archidendron jiringa) varieties from Bengkulu, Indonesia and their potentials as ruminant feed. Biodiversitas 20: 1671-1680. Agricultural waste is abundant in tropical countries. Many farmers in these countries have been using this waste as the main sources for feeding livestock. Ones of them are jengkol (Archidendron jiringa) by-product like peels and leaves have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
2
0
7
Order By: Relevance
“…The UFA could enhance lipid oxidation due to presence of unsaturated bonds and FR [55]. Anthocyanins had hydroxyl groups in the aromatic ring, which can provide extra hydrogen or electron donors and eliminate excessive FR in the body, maintaining PUFA concentration [56]. Buffa et al [57] who demonstrated that phenolic-rich grape marc could improve antioxidant status and decline MDA concentration, as well as increase milk C18:2n-6 level of dairy ewes.…”
Section: Discussionmentioning
confidence: 99%
“…The UFA could enhance lipid oxidation due to presence of unsaturated bonds and FR [55]. Anthocyanins had hydroxyl groups in the aromatic ring, which can provide extra hydrogen or electron donors and eliminate excessive FR in the body, maintaining PUFA concentration [56]. Buffa et al [57] who demonstrated that phenolic-rich grape marc could improve antioxidant status and decline MDA concentration, as well as increase milk C18:2n-6 level of dairy ewes.…”
Section: Discussionmentioning
confidence: 99%
“…Produksi jengkol di Jawa Tengah menempati posisi ke-3 setelah provinsi Lampung, dengan produksi sebanyak 11.127 ton (BPS, 2019). Kulit jengkol memiliki kandungan berbagai senyawa bioaktif seperti tanin, saponin, flavonoid, dan total fenol (Hidayah et al 2019). Buah jengkol terdiri dari dua bagian yaitu kulit jengkol dan biji jengkol.…”
Section: Pendahuluanunclassified
“…Kulit jengkol merupakan salah satu byproduk tanaman pangan yang tidak termanfaatkan dan hanya menjadi sampah sehingga dapat mencemari lingkungan. Hidayah et al [5] melaporkan bahwa kulit jengkol baik dari segi kuantitas dan kualitasnya berpotensi digunakan sebagai bahan supementasi pakan ternak. Proporsi kulit jengkol sebesar 59,99%, sedangkan proporsi bijinya hanya sebesar 40,01%.…”
Section: Pendahuluanunclassified
“…Hasil yang sama juga dilaporkan oleh Anantasook et al [23] bahwa suplementasi senyawa bioaktif dari Terminalia chebula Retz (8,4% tanin terkondensasi dan 9,9% saponin) pada dosis 12 mg secara in vitro menurunkan produksi metan sampai 60.9%. Jadhav et al [24] melaporkan bahwa suplementasi biji teh (0,8; 0,9 dan 1,0% dari konsentrat) menurunkan populasi protozoa (54,6; 57,2; dan 60,6%) dan produksi gas metan (29,0; 33;0 dan 36,0%) secara berurutan pada rasio hijauan dan konsentrat yang berbeda (rendah, medium dan tinggi hijauan) Kulit jengkol mengandung serat kasar sebesar 26,91% dan menurut hasil penelitian Hidayah et al [5] kandungan ligninnya sebesar 15,48-17,85%. Chaves et al [10] menyatakan bahwa kualitas pakan berpengaruh terhadap produksi gas metan (CH4) pada kajian in vitro dimana rendahnya konsentrasi karbohidrat yang tidak berserat pada legume dan hijauan berkontribusi terhadap tingginya produksi gas metan per gram bahan kering yang dikonsumsi.…”
Section: Produksi Gas Metan Proporsi Vfa Parsial Dan Rasio A/punclassified